2009
DOI: 10.1590/s0482-50042009000200010
|View full text |Cite
|
Sign up to set email alerts
|

Rituximabe na síndrome de Felty refratária

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Data on leflunomide are conflicting. While Talip et al reported an increase in neutrophil counts and the possibility of stopping glucocorticoid treatment under leflunomide (starting with leflunomide 100 mg per day for 3 days, followed by 20 mg per day), other case reports did not show any significant efficacy ( 72 , 84 ).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on leflunomide are conflicting. While Talip et al reported an increase in neutrophil counts and the possibility of stopping glucocorticoid treatment under leflunomide (starting with leflunomide 100 mg per day for 3 days, followed by 20 mg per day), other case reports did not show any significant efficacy ( 72 , 84 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Until now, TNFα inhibitors like etanercept, infliximab and adalimumab have not shown any significant improvement in neutrophil counts in several case reports, although synovitis has been treated successfully with these agents ( 71 , 72 , 85 , 86 ). In this context it should be noted, that immunosuppressants with proven efficacy in Felty’s syndrome should be used in any case, even if arthritis is well controlled by the current treatment.…”
Section: Treatmentmentioning
confidence: 99%